2011
DOI: 10.1111/j.1600-0501.2011.02317.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of abutment dis/reconnections on peri‐implant bone resorption: A radiologic study of platform‐switched and non‐platform‐switched implants placed in animals

Abstract: Implants with a PS design show less peri-implant bone resorption during the healing process and as their abutments are disconnected, than do comparably dis/reconnected NPS implants. The location of the PS implant next to a tooth may decrease radiographically visible peri-implant bone resorption significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 22 publications
6
46
0
Order By: Relevance
“…Released titanium particles may act as additional foreign bodies initiating the release of inflammatory mediators associated with bone resorption 70-78 as already described in the case of orthopedic implants. Repeated abutment dis/reconnections, with consequent disruption of the peri-implant soft tissue barrier, have been shown to cause crestal bone resorption around dental implants in animal studies 82,83 and in short-term and long-term clinical investigations as confirmed in several meta-analysis reports. 80 One important aspect that has not been debated in the literature and that has not yet been properly tested is the fact that probing around oral implants could potentially result in trauma to the periimplant soft tissues leading to inflammation, apical proliferation of the epithelium, and consequent bone loss, particularly as it seems like true probing forces and pressures are higher than suggested values from the literature.…”
Section: On Factors With Particular Relevance For Oral and Orthopedmentioning
confidence: 83%
“…Released titanium particles may act as additional foreign bodies initiating the release of inflammatory mediators associated with bone resorption 70-78 as already described in the case of orthopedic implants. Repeated abutment dis/reconnections, with consequent disruption of the peri-implant soft tissue barrier, have been shown to cause crestal bone resorption around dental implants in animal studies 82,83 and in short-term and long-term clinical investigations as confirmed in several meta-analysis reports. 80 One important aspect that has not been debated in the literature and that has not yet been properly tested is the fact that probing around oral implants could potentially result in trauma to the periimplant soft tissues leading to inflammation, apical proliferation of the epithelium, and consequent bone loss, particularly as it seems like true probing forces and pressures are higher than suggested values from the literature.…”
Section: On Factors With Particular Relevance For Oral and Orthopedmentioning
confidence: 83%
“…; Rodriguez et al. ). In particular, matching commercially pure Ti abutments were manipulated altogether 5 times, once a month over a 6‐month period of plaque control.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the degree of inflammation in peri‐implant tissues is lower in one‐piece implants than in two‐piece implants . The micro‐gap between the two components and the disruption of the soft tissues each time they are disconnected and reconnected has an abrupt impact upon the bone resorption that occurs around the implant …”
Section: Introductionmentioning
confidence: 99%